Establishment of the Luoping Biota National Geopark in Yunnan, China - Michael Benton; Shixue Hu; Qiyue Zhang; Tao Xie; Changyong Zhou; Wen Wen; Jinyuan Huang (Geoconservation Research)
Geoparks in China have been a great success story, with 284 national geoparks and 41 of them accorded UNESCO international status, the highest number for any country in the world. We track the progress of one of the geoparks, Luoping Biota National Geopark in Yunnan Province, from initial plans after its discovery as a key site for the exceptional preservation of Middle Triassic marine fossils in 2007, to acceptance as a National Geopark in 2011. Geoparks combine great scientific importance with accessibility and attraction for tourists. The scientific importance of Luoping is in the fossils, thousands of specimens of marine invertebrates, fishes and reptiles, together with rare elements from land (e.g. insects, plants), representing an important phase in the Mesozoic Marine Revolution, when life was recovering from devastation at the end of the Permian, and 8 million years later, had developed stable ecosystems with a new structure, dominated by predatory fishes and reptiles. The touristic importance of the Luoping Biota Geopark has already been demonstrated by rapid development of facilities and high visitor numbers.